Mason's world dictionary of livestock breeds, types and varieties (CABI Pub., 2002)
This is a new edition of Mason's standard reference text, and contains key breed information about cattle, sheep, pigs, goats, horses, asses and buffalo. It contains approximately 9000 entries and cross-references, on breeds, sub-breeds, types, varieties, strains and lines of these species. The aim is to include all the livestock names that may be encountered in international literature. It is an essential reference book for all those concerned with domestic livestock.